Perbedaan Perencanaan Karir Siswa Kelas X Madrasah Aliyah Darul Hikmah Pekanbaru Sebelum Dan Sesudah Diberi Layanan Informasi Tahun Ajaran 2013/2014 - Mayanti, Pelda; Asyari, Abu; Rosmawati, Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : The purpose of this study is 1) To describe the career planning student of before the implementation of information service, 2) To describe the career planning student of after the implementation of information service, 3) To determine difference between the career planning student before and after the implementation of the information service, 4) To determine the effect of the information service to the career planning student. The menthod used was experimental quasi with One group pattern: One group pre-test and post test design. The tool used in collecting the data was a questionnaire. The samples were taken using simple random sampling technique which amoun to 65 people. The data is analyzed using a percentage formula; the ‘’t’’ test was used to distinguish the career planning student before and after the implementation of the information service. From the calculation of the ‘’t’’ test, it was obtained that the thitung greater than ttabel with (-18,16>1,960) at the level error of 5%. Which means that in this study, there difference between the career planning student before and after the application of information service. From the calculation of the product moment correlation, it is found that r = 0,74 is the determinant coefficient of r2 = 0,54. This, it can be seen that the effect of information service on the career planning student is 54%. Based on the result of this research, it can be that the improvement career planning student after being given the information service.Keyword: Career planning, Information service